2010
DOI: 10.1002/oti.302
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of workers with chronic pain in Brazil and its social consequences

Abstract: Chronic pain contributes towards less diversified participation centred on household activities, fewer social relationships and smaller number of recreational activities. The aim of the study was to further investigate the effects of chronic pain on participation, focusing on how workers deal with the experienced restrictions. Ten workers with chronic pain participated in the survey, which was conducted with qualitative interviews. Analyses of thematic units revealed that chronic pain has consequences for part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
0
15
0
9
Order By: Relevance
“…The team members did not agree over 24 papers and sent these to two other team members for a decision. Sixteen studies were excluded after quality appraisal, [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] hence 77 papers were included reporting 60 studies. These studies explored the experiences of 1168 adults ranging from 18 to 91 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…The team members did not agree over 24 papers and sent these to two other team members for a decision. Sixteen studies were excluded after quality appraisal, [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] hence 77 papers were included reporting 60 studies. These studies explored the experiences of 1168 adults ranging from 18 to 91 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of work leads the worker to rely on third parties for their livelihood, in addition to feelings of failure and low productivity 8 . A qualitative study with workers in rehabilitation process showed that leaves, unemployment, or retirement can cause suffering associated with the loss of the social role as a worker 9 . Thus, the restriction of labor activities influences the quality of life, with the individual outside the labor market being also excluded from other social networks, and inserted into a vulnerabilization path 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain may lead to changes in lifestyle, drug dependence, social isolation, impairment of identity and selfesteem. In this process, some occupational roles are impaired and individuals may develop a feeling of inutility 4 . Other consequences of chronic pain are emotional changes, difficulty to perform daily activities 5 , difficulties at work which may lead to medical leave, unemployment or retirement and, as consequence, distress for losing their role as ORIGINAL ARTICLE DOI 10.5935/1806-0013.20160064 workers 4,6 .…”
Section: Introductionmentioning
confidence: 99%
“…In this process, some occupational roles are impaired and individuals may develop a feeling of inutility 4 . Other consequences of chronic pain are emotional changes, difficulty to perform daily activities 5 , difficulties at work which may lead to medical leave, unemployment or retirement and, as consequence, distress for losing their role as ORIGINAL ARTICLE DOI 10.5935/1806-0013.20160064 workers 4,6 . A study carried out in Salvador has shown that 41.4% of its population suffer with chronic pain and that the highest prevalence is among middle-aged adults (40 to 49 years old) 7 .…”
Section: Introductionmentioning
confidence: 99%